Formulation, Optimization and Evaluation of Naringenin Loaded Cubosomes for Effective Management of Alzheimer's Disease - Raut, Yashowardhan; Sutar, Kishori Prasanna; Hooli, Shivaraj; Naik, Gautam; Udagatti, Vinayak (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: The goal of this work was to formulate a stable naringenin-loaded cubosomal in situ gel to improve naringenin absorption into the brain by direct nose-to-brain transfer. Materials and Methods: This investigation aimed to prepare, optimize and evaluate a cubosomal in situ gel containing naringenin, aimed at facilitating the delivery of the drug to the brain via nasal administration. Cubosomes were fabricated using a top-down methodology and optimization was conducted using 32 factorial designs. Cubosomes were analyzed for particle size, encapsulation efficiency, zeta potential and cumulative percent drug release. Poloxamer-407 was used as a thermoreversible and mucoadhesive polymer for preparing naringenin-loaded cubosomal in situ gel. Results: The optimized cubosome formulation (F3) containing 3% Glyceryl Monooleate (GMO) and 1.5% poloxamer, exhibited a particle size of 123.2 nm, an encapsulation efficiency of 71.12% and a zeta potential of -38.61. The Transmission Electron Microscopy (TEM) image represented the smooth cubic structure of naringenin-loaded cubosomes. The thermoreversible in situ gel demonstrated appropriate gelation temperatures, viscosities, pH levels and in vitro drug diffusion characteristics. The in vitro drug diffusion study revealed a higher percentage cumulative drug release, reaching 82.21%. Conclusion: The results obtained demonstrated enhanced capability of the developed naringenin-loaded cubosomes to facilitate drug permeation through the nasal cavity.
Keywords: Alzheimer’s disease; Brain targeting; Cubosomes; Naringenin; Nasal delivery